Gas bubble formation in fermenting and non-fermenting yeasts - Kgotle, Evodia Yolander (University of the Free State, 2016)
Literature previously suggested that intracellular gas bubble formation cannot occur in microorganisms even under high gas supersaturation. This observation was disproved with the discovery of gas bubbles in the yeasts Saccharomyces cerevisiae (baking industry) and Saccharomyces pastorianus (Brewing industry). As a result the missing link between the excessive production of carbon dioxide (CO2) by alcoholic fermentation inside the yeast cells and the vigorous release of this CO2 into the surrounding environment was uncovered. Further investigations proved that CO2 was indeed the gas contained inside these gas bubbles yet additional analysis of this gas composition was still needed. Here we investigate the occurrence of gas bubbles in yeasts that are fermenting and non-fermenting to identify any occurring differences and conserved status of gas bubbles formation in yeasts. Gas bubbles occurring in Crabtree-positive fermenting yeasts were observed to be more than those formed in the other yeasts (Crabtree-negative and strictly respiring yeasts). Although this was observed only on fermentable media, while on non-fermentable media less or no gas bubbles were formed. Furthermore, the Crabtree-negative fermenting and strictly respiring yeasts revealed similar results on both fermentable and non-fermentable media, with little to no gas bubble formation. Gas composition analysis was also carried out on three Crabtree-positive yeasts and it indicated the occurrence of five elements that were expected to be present in our samples. Moreover detection of sulphur compounds was observed in the same three samples with varying intensities. Nonetheless further research is still needed to confirm the point of production for these compounds, using more specific and sensitive techniques. From these findings it can be concluded that gas bubble formation is conserved in yeasts, with the amount of bubbles formed depending on the mode of CO2 production. In addition, it is possible that other gases or compounds such as sulphur compounds can be contained inside these gas bubbles.

Literatuur tot dusver het voorgestel dat intrasellulêre gasborrels nie in mikroörganismes kan voorkom nie, selfs nie onder toestande van hoë gas- superversadiging nie. Hierdie waarneming is egter verkeerd bewys met die ontdekking van gasborrels in die giste Saccharomyces cerevisiae (bakkersbedryf) en Saccharomyces pastorianus (brouersbedryf). Die ontbrekende skakel tussen die uitermatige vorming van koolstofdioksied (CO2) tydens alkoholiese fermentasie binne die gisselle en die hoë tempo van CO2 vrystelling na die omliggende omgewing is ontdek. Verdere ondersoek het bewys dat CO2 inderdaad die gas is wat die borrels vul, alhoewel die gassamestelling verder ondersoek moes word. Hier vergelyk ons die teenwoordigheid van gasborrels in gis wat fermenteer met die teenwoordigheid van gasborrels in gis wat nie fermenteer nie om die status van borrelvorming in hierdie giste te bepaal. Meer gasborrels het in Crabtree-positiewe fermenterende gis gevorm wanneer hierdie gis met ander gis vergelyk is (Crabtree-negatiewe fermenterende gis en slegs-respirerende gis). Hierdie verskynsel geld egter net wanneer fermenterende gis op fermenteerbare medium gegroei is, groei op nie-fermenteerbare medium het minder of geen borrels tot gevolg gehad. Verder het die groei van Crabtree-negatiewe fermenterende gis en slegs-respirerende gis op fermenteerbare medium soortgelyke resultate as met groei op nie-fermenteerbare medium gelewer, met geen of min borrelvorming. Die samestelling van die gas in borrels van drie Crabtree-positiewe fermenterende giste is bepaal en die teenwoordigheid van vyf elemente is vasgestel, soos wat verwag is. Verder is die teenwoordigheid van swaelverbindings in dieselfde drie monsters waargeneem maar het egter in hoeveelheid gewissel. Verdere ondersoek met meer spesifieke en sensitiewe toerusting is egter nodig om die hoeveelheid wat gevorm word te kan bevestig. Vanuit hierdie waarnemings kan daar afgelei word dat gasborrel-vorming gekonserveerd is in gis en dat die hoeveelheid borrels wat vorm afhang van die wyse waarop CO2 gevorm word. Bykomstig is dit moontlik dat ander gasse of verbindings, soos swaelverbindings, deel kan vorm van die inhoud van hierdie borrels.
Dissertation ((M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2016
Keywords: Carbon dioxide; Crabtree-negative; Crabtree-positive; Fermentation; Intracellular gas bubbles; NanoSAM; Respiration; Sulphur compounds